Assessment of textile craft products’ creativity in the Latvian competition for pupils - Urdziņa-Deruma, Māra (FormAkademisk, 2018)
The purpose of the research is to explore the results of pupils’ creative activity in a competition in textile craft in Latvia and to find trends in the creation of textile craft products. The applied method is the analysis of creative work items made by pupils from Forms 6–7 (N1 = 106) and Forms 8–9 (N2 = 132): photos, designs and textile craft products. Among the hand and foot garments, the most popular products in both age groups were fingerless gloves. The knitting technique was used most frequently, and most of the items were wearable. Creativity predominantly manifested in the combinations of colours, techniques and materials, followed by creative technology solutions and creative product shapes. The results regarding creativity were higher for the creation of textile craft products than for creating designs.